Quality improvement of common carp (Cyprinus carpio L.) meat fortified with n-3 PUFA. (May 2020) - Sobczak, M.; Panicz, R.; Eljasik, P.; Sadowski, J.; Tórz, A.; Żochowska-Kujawska, J.; Barbosa, V.; Domingues, V.; Marques, A.; Dias, J.
Abstract: The effect of carp feeding with n-3 PUFA-enriched feed ( Schizochytrium sp. meal or salmon oil) on nutritional quality indicators (proximal composition, fatty acid profile of fat) and culinary quality (color parameters, texture, sensory properties) was evaluated. Highly significant effects of carp nutrition on chemical composition and fat characteristics, L* and a* color parameters, muscle fiber size, endomysium thickness, moisture and taste of fillets were determined. Fillets obtained from carps fed with the experimental feed contained less protein and more crude fat and had larger muscle fibers, but scored more highly in the sensory evaluation of moisture and fishy taste. In the fat of carp fed the enriched feed, a greater share of total PUFA, n-3 PUFA, total EPA and DHA, n-3/n-6 ratio, and a smaller share of total MUFA were observed compared with control fish. However, no effect of nutrition on the texture of carp fillets, assessed either instrumentally or using sensory methods, was found. The use of Schizochytrium sp. meal as a source of EPA and DHA gave much better results than salmon oil, as it allowed a higher content of these valuable fatty acids to be achieved, without compromising quality. Highlights: Schizochytrium sp. meal in common carp diet improved nutritional value of fillets. Supplementation of feed for carp can significantly improve fish fatty acid profile. Schizochytrium sp. meal showed greater potential in carp feeding than salmon oil.